Shear Behavior of Concrete Beams Strengthened with CFRP Grid and PCM Shotcrete - Andi Arwin Amiruddin (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2019)
The results of an experimental and analytical study of the shear behavior of damaged or under-strength concrete beams strengthened with carbon fiber reinforced plastics (CFRP) grid and polymer cement mortar (PCM) shotcrete describes in this paper. The aim of this study is to evaluate shear performances of reinforced concrete beams retrofitted by using PCM shotcrete and CFRP grid. Four concrete beams reinforced internally with steel and externally with both PCM and CFRP grid (longitudinal direction used CR-10 and transversal direction used CR-6) applied to the specimens were tested under three-point bending. The shear failure is initiated by a major diagonal crack within the beam shear span. This diagonal crack extended horizontally at the level of the CFRP grid. Results show that PCM shotcrete with CFRP grid is very effective for shear strengthening. Increases in strength of 140% for PGB over the RCB as control, un-retrofitted beams were noted.